Non-invasive Brain Stimulation for Chronic Pain: State of the Art and Future Directions - Xiong, Huan-Yu; Zheng, Jie-Jiao; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
As a technique that can guide brain plasticity, non-invasive brain stimulation (NIBS) has the potential to improve the treatment of chronic pain because it can interfere with ongoing brain neural activity to regulate specific neural networks related to pain management. Treatments of chronic pain with various forms of NIBS, such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), using new parameters of stimulation have achieved encouraging results. Evidence of moderate quality indicates that high-frequency rTMS of the primary motor cortex has a clear effect on neuropathic pain and fibromyalgia. However, evidence on its effectiveness regarding pain relief in other chronic pain conditions is conflicting. With regard to tDCS, evidence of low quality supports its benefit for chronic pain treatment. However, evidence suggesting that it exerts a small treatment effect on neuropathic pain and headaches is also conflicting. In this paper, we describe the underlying principles behind these commonly used stimulation techniques; and summarize the results of randomized controlled trials, systematic reviews, and meta-analyses. Future research should focus on a better evaluation of the short-term and long-term effectiveness of all NIBS techniques and whether they decrease healthcare use, as well as on refinement of selection criteria.